Forbearance, resolution and deposit insurance - Martin F. Hellwig; André Sapir; Marco Pagano; Viral V. Acharya; Leszek Balcerowicz; Arnoud Boot; Markus K. Brunnermeier; Claudia Buch; Ieke van den Burg; Charles Calomiris; Daniel Gros; Dario Focarelli; et al. (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2012)
The report discusses a variety of issues involving difficulties in the banking sector, with a view to ascertaining the appropriate institutional infrastructure in the context of the European Union and the euro area. Forbearance on the part of banks dealing with delinquent borrowers is problematic if it is designed as a way to game creditors and supervisors. Supervisors should not tolerate excessive forbearance; failure to intervene early tends to increase the costs of the crisis. Macro-prudential concerns should not induce the authorities to delay clean-ups of banks in difficulties. To minimise the macroeconomic fallout from banking problems and to reduce the temptation for authorities to delay and hide problems in banking, it is necessary to have a viable resolution regime that leaves room for authorities to reduce the systemic fallout from resolution. The Advisory Scientific Committee calls for the establishment of strong European bodies responsible for banking supervision and bank resolution. A European competence is necessary to ensure that cross-border concerns are given appropriate weight in supervision and resolution.
Keywords: G28; G33; 330; loan forbearance; bank resolution; bank regulation